PENGARUH PENAMBAHAN SERAT ECENG GONDOK PADA KUAT TEKAN PAVING BLOCK K-200 - Muttaqin Fauzin Istighfarin; Rasio Hepiyanto (Kadiri University, 2019)
This study aims to know and analyze how strong the influence of additional water hyacinth fiber to the compressive strength of the K-200 paving block. The method used in this study is the experimental method, with the comparison of mix design referring to the comparison of concrete quality mixture K-200 (SNI 7394-2008). The result is K-200 paving block decreases its compressive strength after given the mixture of water hyacinth fiber. The percentage of the lowest decrease is in the 0,2 mixture of 55,69% and the highest decrease is in the mixture of 0,8 with the declining percentage of 82,39%. The score of compressive strength for each test object is: Normal of 209,53 kg/cm², 2% of 92,86 kg/cm², 4% of 84,53 kg/cm², 6% of 58,33 kg/cm², and 8% of 36,90 kg/cm². The relationship of non-linear regression can be seen in R² = 1 on polynomial order 4. Paving block with code objects test “Normal” classified as in the quality of paving block B with compressive strength of 209,53 kg/cm² (17,03 Mpa), while for paving block with extra water hyacinth fiber, it is below the compressive strength standard according to SNI 03-0691-1996. Keywords: Rigid Pavement; Paving Block; Water Hyacinth; Compressive StrengthPenelitian ini bertujuan untuk mengetahui dan menganalisis seberapa kuat pengaruh penambahan serat eceng gondok terhadap kuat tekan paving block K-200. Metode yang digunakan dalam penelitian ini adalah metode eksperimen, dengan perbandingan rujukan desain campuran dengan perbandingan kualitas campuran beton K-200 (SNI 7394-2008). Hasilnya adalah paving block K-200 mengurangi kekuatan tekannya setelah diberi campuran serat eceng gondok. Prosentase penurunan terendah adalah pada campuran 0,2 sebesar 55,69% dan penurunan tertinggi pada campuran sebesar 0,8 dengan presentase penurunan sebesar 82,39%. Skor kuat tekan untuk setiap benda uji adalah: Normal 209,53 kg / cm², 2% dari 92,86 kg / cm², 4% dari 84,53 kg / cm², 6% dari 58,33 kg / cm², dan 8% dari 36,90 kg / cm². Hubungan regresi non-linear dapat dilihat pada R² = 1 pada polinomial orde 4. Paving block dengan dengan kode objek tes